2021
DOI: 10.3390/cells10113098
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Identification and Clinical Validation of a Novel Long Non-Coding RNA/mRNA/miRNA Molecular Network for Potential Biomarkers for Discriminating SARS CoV-2 Infection Severity

Abstract: (1) Background: The coronavirus (COVID-19) pandemic is still a major global health problem, despite the development of several vaccines and diagnostic assays. Moreover, the broad symptoms, from none to severe pneumonia, and the various responses to vaccines and the assays, make infection control challenging. Therefore, there is an urgent need to develop non-invasive biomarkers to quickly determine the infection severity. Circulating RNAs have been proven to be potential biomarkers for a variety of diseases, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 73 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…72 Hsa-miR-4257 was downregulated in COVID-19 patients versus controls and in severe versus mild COVID-19 as reported by Agwa and colleagues. 73 ROC analysis revealed that hsa-miR-4257 expression could be used as biomarker to distinguish COVID-19 patients from controls with an AUC of 0.911. 73 Differential expression of two miRNAs was found by using whole serum of patients with severe and non-severe COVID-19, whereas ten distinct differentially expressed miRNAs were identified when using extracellular vesicles isolated from sera (Table 1).…”
Section: Diagnostic Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…72 Hsa-miR-4257 was downregulated in COVID-19 patients versus controls and in severe versus mild COVID-19 as reported by Agwa and colleagues. 73 ROC analysis revealed that hsa-miR-4257 expression could be used as biomarker to distinguish COVID-19 patients from controls with an AUC of 0.911. 73 Differential expression of two miRNAs was found by using whole serum of patients with severe and non-severe COVID-19, whereas ten distinct differentially expressed miRNAs were identified when using extracellular vesicles isolated from sera (Table 1).…”
Section: Diagnostic Biomarkersmentioning
confidence: 99%
“…Hsa-miR-4257 was downregulated in COVID-19 patients versus controls and in severe versus mild COVID-19 as reported by Agwa and colleagues. 73 ROC analysis revealed that hsa-miR-4257 expression could be used as biomarker to distinguish COVID-19 patients from controls with an AUC of 0.911. 73…”
Section: Mirnas In Blood Associated With Covid-19 Disease Severitymentioning
confidence: 99%
See 1 more Smart Citation
“… 47 , 48 Circulating profiles of plasma microRNAs (miRNA) in particular have been shown to be tightly associated with disease and capable of providing not only detailed prognostic information but also mechanistic insight. 49 , 50 Indeed, circulating miRNAs are emerging as a potential biomarker for SARS-CoV-2 infection, 51 , 52 , 53 and may even be involved in regulating disease phenotypes, 54 and may be considered in novel treatments. 55 , 56 Whether miRNAs can be used as a prognosticator for disease severity and mortality in vulnerable groups such as patients with CVD remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have identified associations between acute infection and the host response [17,18]. Other studies have evaluated associations between disease severity and aspects of the adaptive immune system [19][20][21][22][23] and quantified viral RNA [24][25][26][27][28][29]. A recent study has used neural networks to predict patient survival outcomes with high accuracy [30], which can be useful when whole transcriptome data are available.…”
Section: Introductionmentioning
confidence: 99%